(untitled) (Research, Society and Development, 2018)
Compared to most exercise and sports activities, street racing is highly versatile as it can be performed in a wide variety of indoor or outdoor environments, on lane or uneven terrain. Physical exercise is usually associated with the well-being of its practitioners. Many people who seek healthier lifestyle habits, such as controlling body weight and improving physical fitness, end up choosing the race as a modality. Among its various manifestations, the race is one of the modalities with many fans, both for ease in its practice, as well as for the health benefits and the low cost. To verify the prevalence of injuries in amateur street runners that cover up to 10 km. A quantitative research was carried out through a semi-structured questionnaire with open questions. Included in this study were amateur athletes who had been racing for at least three months, at least twice a week, and were 18 years of age or older. A total of 70 questionnaires were sent, of which 30 were viable. Eight participants are women and 22 are men. Most respondents do not do pre-employment pre-race work. Among men, 14 had some type of injury or sensation of pain. Among women only 4. Amateur street runners that cover up to 10 km have mostly knee injuries, being present in women the calf, thigh and ankle injuries.